Clinical and laboratorial outcomes of xenogeneic biomaterials: literature review - de Azambuja Carvalho, Pedro Henrique [UNESP]; de Oliveira Ciaramicolo, Nathaly; Ferreira Júnior, Osny; Pereira-Filho, Valfrido Antonio [UNESP] (AME Publishing Company, 2023)
Background and Objective: Bone regeneration procedures are an important part of oral and maxillofacial surgery development, With the rising of dental implants research and techniques, bone augmentation became an essential also for oral implantology. The aim of this review was to, screen up the origins and the innovations through its laboratorial and clinical applications of xenografts. Methods: A comprehensive search, without date limit was performed in MEDLINE, SCOPUS, Cochrane and Web of Science databases between November 2020 and March 2021, systematic reviews, human studies, clinical reports, in vivo and in vitro studies regarding history, application, outcomes or innovations in xenogeneic bone grafts usage were included, after initial search a manual cross-reference search was performed in the included papers. Key Content and Findings: Xenogeneic grafts have been pointed as one of the most reliable alternatives to autogenous bone in augmentation techniques. Conclusions: Xenogeneic grafts have been pointed as one of the most reliable alternatives to autogenous bone in augmentation techniques, but most of the applications were based on empirical expertise, and there is no consensus about its properties, fabrication methods and biological mechanisms which leads to clinical success. Clinical and pre-clinical research still necessary to comprehend the properties and gold standard applications of Xenografts.
Keywords: alveolar ridge augmentation; bone substitutes; Xenogenous bone; xenografts, heterografts